2017
DOI: 10.1016/j.egja.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Perineural versus intravenous clonidine as an adjuvant to Bupivacaine in supraclavicular Brachial plexus block

Abstract: Background: Clonidine has been used as an adjuvant in Brachial plexus block (BPB) to enhance its quality and duration. However, whether, clonidine in BPB acts perineurally or via systemic absorption is not entirely clear. Methods: Ninety-three patients of either sex, ASA I and II, aged 18-70 years, undergoing lower end humerus fracture fixation were included in the study. Patients were randomized into 3 groups. All the patients received brachial plexus block using nerve stimulator with 28 ml 0.5% Bupivacaine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The results of the present study are similar to those reported earlier studies by Baj et al (2013), 3 Ahmed NU et al (2011), 10 Kohli et al (2013), 11 Jaiswal et al (2013) 12 V. Bedi et al (2017) 9 who found that the significant prolongation of mean total duration of sensory and motor block occured in which clonidine given perineurally. Time to first rescue analgesia (duration of analgesia) Mean duration of analgesia was longest in perineural clonidine group C (8.12±1.22 hrs) in comparison to group A (statistically significant p value 0.001) and it might be due to that clonidine enhance sensory and motor nerve blockade by three possible mechanism: (1) clonidine block conduction of C and A delta fibers and increase potassium conductance and intensifies conduction block of local anaesthetics, (2) clonidine may cause local vasoconstriction thereby reducing vascular removal of local anaesthetic surrounding neural structures, and (3) primary spinal site of action of alpha 2 adrenergic agonist for analgesia and a mutifactorial mechanism of action enhancing peripheral or intraspinal blockade from local anaesthetics.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the present study are similar to those reported earlier studies by Baj et al (2013), 3 Ahmed NU et al (2011), 10 Kohli et al (2013), 11 Jaiswal et al (2013) 12 V. Bedi et al (2017) 9 who found that the significant prolongation of mean total duration of sensory and motor block occured in which clonidine given perineurally. Time to first rescue analgesia (duration of analgesia) Mean duration of analgesia was longest in perineural clonidine group C (8.12±1.22 hrs) in comparison to group A (statistically significant p value 0.001) and it might be due to that clonidine enhance sensory and motor nerve blockade by three possible mechanism: (1) clonidine block conduction of C and A delta fibers and increase potassium conductance and intensifies conduction block of local anaesthetics, (2) clonidine may cause local vasoconstriction thereby reducing vascular removal of local anaesthetic surrounding neural structures, and (3) primary spinal site of action of alpha 2 adrenergic agonist for analgesia and a mutifactorial mechanism of action enhancing peripheral or intraspinal blockade from local anaesthetics.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings corroborate by Singelyn et al (1992) 17 and V. Bedi et al (2017). 9 Mean VAS Score in present study remained less than 4 throughout the study period showing adequate postoperative analgesia in the all the four groups. Overall value of mean VAS score was significantly more in group A (1.88±0.13) as compared to group C (1.33±0.22).…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Thirty-three trials compared clonidine in doses of 30-180 µg with placebo in 1975 patients, 12−44 three of the trials included a systemic clonidine group. 14,21,39 Fifty-six trials compared dexmedetomidine in doses of 30-100 µg with placebo in 3243 patients, 5,31,42,45−94 six of the 53 trials included a systemic dexmedetomidine group. 45,[63][64][65]78,80 Nineteen trials compared dexmedetomidine with clonidine in 1130 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%